Investigating 99Mo output changes in high-sustainability uranium targets by modifying target volume and geometry - Raposio, Robert; Braoudakis, George; Rosenfeld, Anatoly; Bedwell-Wilson, Juniper; Thorogood, Gordon (Frontiers in Nuclear Engineering, 2023)
The most common current uranium target type for 99Mo production uses plate geometry. MCNP6.2 was used to model rectangular, spherical, and cylindrical targets ranging from 12.03cm3 to 120.34cm3 to determine the target geometry and volume effects on 99Mo output, sustainability, proliferation concerns, and heating. 4-7 days irradiation was used with a consistent target density of 2g/cm3 UO2 for all target types. The cylindrical target was found to have the best performance due to having the second highest sustainability, the highest 99Mo output and produce the lowest amounts of 239Pu compared to the other target geometries. The heating comparison showed that there were negligible heating concerns for all target volumes and geometries.